OPTIMIZING MATHEMATICS LEARNING IN FIFTH GRADES: THE CRITICAL ROLE OF EVALUATION IN IMPROVING STUDENT ACHIEVEMENT AND CHARACTER - Yusron Abda'u Ansya; Ayu Alfianita; Hanna Putri Syahkira; Syahrial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
The aim of this research is to describe the role of learning evaluation in fifth grade elementary school mathematics subjects. This research was conducted on Fifth-Grades students of UPT SD Negeri 060809 Medan Kota. The research method used in this research is descriptive qualitative. The subjects in this research are Fifth-Grades students and Fifth-Grades teachers and the objects in this research are the results of interviews and observations. Data collection techniques in this research are interviews with students and teachers, conducting classroom observations, analyzing supporting documents and literature studies. The data analysis technique used in this research is content analysis. The research results show that evaluation of mathematics learning in Fifth Grades of SD Negeri 060809 Medan Kota has an important role in measuring learning achievement, providing feedback, identifying weaknesses and strengths, and directing learning improvements. The evaluation instruments used include oral tests, assignments and portfolios. Apart from that, evaluation also aims to measure academic achievement and character, foster multicultural awareness, and encourage the application of values in real contexts. Furthermore, evaluation also plays a role in developing student learning competencies by measuring student progress, identifying their learning needs, and planning appropriate interventions. It also involves providing constructive feedback, developing metacognitive skills, and encouraging reflection and continuous improvement for students.